2012
DOI: 10.1002/poc.1941
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of acenes: mechanisms and dependence on acene length

Abstract: Acenes are polycyclic aromatic hydrocarbons consisting of linearly fused benzene rings. These compounds are currently the subject of great interest from both fundamental and applied perspectives, particularly for use in organic electronics. This review highlights the computational studies carried out to understand acene reactivity, their reaction mechanisms, and the relationship of the latter to acene length. Generally, as acene length increases, the reactivity of acenes increases, and a greater tendency towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 91 publications
(201 reference statements)
4
77
0
Order By: Relevance
“…The color of the solution changed from purple to red over a period of hours, even when protected from air and light, in accord with loss of the acene chromophore. This behavior is consistent with what we, and others [19], have observed in other pentacene systems, and the constitution of the decomposition product(s) was not pursued. This instability is disappointing, but not completely unexpected, as Stillmann and coworkers have demonstrated that the acene chromophore is destroyed rather rapidly in solution [17a], when porphyrins are appended to the pro cata positions of 6,13-diphenyl pentacene, likely through addition of oxygen [19].…”
Section: Synthesis Of Pentacene-porphyrin Dyadssupporting
confidence: 92%
“…The color of the solution changed from purple to red over a period of hours, even when protected from air and light, in accord with loss of the acene chromophore. This behavior is consistent with what we, and others [19], have observed in other pentacene systems, and the constitution of the decomposition product(s) was not pursued. This instability is disappointing, but not completely unexpected, as Stillmann and coworkers have demonstrated that the acene chromophore is destroyed rather rapidly in solution [17a], when porphyrins are appended to the pro cata positions of 6,13-diphenyl pentacene, likely through addition of oxygen [19].…”
Section: Synthesis Of Pentacene-porphyrin Dyadssupporting
confidence: 92%
“…Interestingly, the enthalpy of dehydrogenation of 6,13-dihydropentacene (11) is now (almost) identical to the Δ dehydr H for conversion of cyclohexane to cyclohexene, thus clearly demonstrating the high reactivity (e.g., in addition reactions) of the center ring of pentacene. 12 The tautomeric equilibrium ratios are determined by Δ t G and not only by Δ t H. It may be expected that the molecular entropy increases in the conversion of the methylenedihydroacene to the methylacene due to the formation of an internal (free) methyl rotor. At first approximation, the contribution of a free rotating methyl group to the molecular entropy, S 0 , at 298 K, can be estimated as 5.8 cal mol −1 K −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, a simple heterojunction photovoltaic device using 6 as an electron donor and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) as an electron acceptor has been successfully fabricated by us. [17] The results showed that compound 6 could be a chargetransport material in organic semiconductor devices.…”
Section: Dienesmentioning
confidence: 99%
“…[5] However, larger acenes, with more than five linearly fused benzene rings, show poor stability, which hampers the possible device applications. [6] To improve the stability, many kinds of bulky groups and electron-withdrawing groups (e.g., phenyl, [7] arylthio, [8] alkylsilylethynyl, [9] and fluoro [10] ) have been introduced onto the skeleton of acenes. The reported structural modifications have been proven to enhance the stability of acenes and the efficiency of the devices.…”
Section: Introductionmentioning
confidence: 99%